Performance of STAR-RIS-Aided RSMA Networks: Impact of Correlated Fading Channels and SIC Imperfections - Eduardo Goncalves Gomes; Henry Ramiro Carvajal Mora; Edgar Eduardo Benitez Olivo (IEEE Access)
This paper investigates the outage performance of the downlink of a wireless network, where a base station communicates with two users using the Rate-Splitting Multiple Access (RSMA) protocol. To overcome obstacles that block direct transmission, a simultaneous transmitting and reflecting reconfigurable intelligent surface (STAR-RIS) is used to enable communication. The users are positioned on opposite sides of the STAR-RIS, which operates under a mode-switching protocol, assigning elements for either transmission or reflection. The channels are assumed to undergo Rician fading, and the system performance is analyzed considering the correlation effects caused by closely spaced STAR-RIS elements, for which the model employed to generate correlated channels is introduced. Additionally, at the users’ receiver side, we consider that the decoding of users’ messages is subject to imperfect successive interference cancellation (SIC). An approximate analytical expression is also derived for the scenario with uncorrelated STAR-RIS elements and imperfect SIC. Monte-Carlo simulations further explore the system performance, focusing on key parameters such as the number of STAR-RIS elements, channel-correlation factor, power allocation factors of common and private streams relative to the RSMA protocol, and error factor of imperfect SIC. This work’s contributions provide a deeper understanding of the impact of correlated channels and imperfect SIC on STAR-RIS-aided networks, offering insights for optimizing performance under realistic deployment conditions.